Operation performance and microbial community dynamics of phosphorus removal sludge with different electron acceptors. (1st July 2014) - Lv, Xiaomei; Shao, Mingfei; Li, Chaolin; Li, Ji; Liu, Dongyang; Gao, Xinlei; Xia, Xue
Abstract: Operation performances of phosphorus removal sludge with different electron acceptors in three parallel SBRs were firstly compared in the present study, and the effect of post-aeration on denitrifying phosphorus removal was also studied. Moreover, community dynamics of different phosphorus removal sludge was systematically investigated with high-throughput sequencing for the first time. TP removal rates for nitrate-, nitrite-, and oxygen-based phosphorus removal sludge were 84.8, 78.5, and 87.4 %, with an average effluent TP concentration of 0.758, 0.931, and 0.632 mg/l. The average specific phosphorus release and uptake rates were 20.3, 10.8, and 21.5, and 9.43, 8.68, and 10.8 mgP/(gVSS h), respectively. Moreover, electron utilization efficiency of denitrifying phosphorus removal sludge with nitrate as electron acceptor was higher than nitrite, with P/e − were 2.21 and 1.51 mol-P/mol-e −, respectively. With the assistance of post-aeration for nitrate-based denitrifying phosphorus removal sludge, settling ability could be improved, with SVI decreased from 120 to 80 and 72 ml/g when post-aeration time was 0, 10, and 30 min, respectively. Moreover, further phosphorus removal could be achieved during post-aeration with increased aeration time. However, the anoxic phosphorus uptake was deteriorated, which was likely a result of shifted microbial community structure. Post-aeration of approximately 10 min was proposed for denitrifying phosphorus removal. Nitrate- and nitrite-based denitrifying phosphorus removal sludge exhibited similar community structure. More phosphorus accumulating organisms were enriched under anaerobic–aerobic conditions, while anaerobic–anoxic conditions were favorable for suppressing glycogen-accumulating organisms. Significant differences in pathogenic bacterial community profiles revealed in the current study indicated the potential public health hazards of non-aeration activated sludge system.